"No Bodies to Kick or Souls to Damn": The Political Origins of Corporate Criminal Liability. Issue 1 (April 2021) - Grasso, Anthony
Abstract: Research on corporate criminal law has grown since the Great Recession, but corporate criminal liability, the principle charging corporations for crimes, remains understudied. Literature points to a 1909 Supreme Court decision as its basis, but historical analysis of the doctrine's deeper political roots reveal that its development was contingent on the convergence of several unique factors driving turn of the century American politics. First, corporate criminal liability would not have emerged had it not been for shifts in jurisprudential theory reconceptualizing the corporate form as an independent entity. Second, middle managers of railroads emerged as powerful political players during this period who capitalized on this discursive shift to advocate for corporate criminal liability as an alternative to individual liability rules directed against them. Third, the Supreme Court upheld corporate criminal lability in 1909 because it was constructed by the era's Republican majority to protect the party's economic preferences, and corporate criminal liability was viewed as consistent with their conservative agenda. These factors were each necessary, but alone insufficient, in paving the way for the Court to validate the principle in 1909. How they fit together sequentially illuminates how the doctrine's construction was contingent on specific political and historical circumstances.